Quadratus lumborum block for analgesia after caesarean section: a randomised controlled trial. (15th September 2019) - Irwin, R.; Stanescu, S.; Buzaianu, C.; Rademan, M.; Roddy, J.; Gormley, C.; Tan, T.
Summary: Quadratus lumborum block has been shown to provide satisfactory analgesia after caesarean section performed under neuraxial anaesthesia. However, its efficacy has not been demonstrated in patients who have received intrathecal morphine. The aim of this study was to assess the efficacy of quadratus lumborum block as part of a multimodal analgesic regimen including intrathecal morphine. This was a prospective, double‐blind, placebo‐controlled trial. Participants were randomly allocated to receive bilateral quadratus lumborum block (40 ml levobupivacaine 0.25%) or sham block (control) after undergoing elective caesarean section under spinal anaesthesia. The primary outcome was 24‐h morphine consumption measured by patient‐controlled analgesia. Secondary outcomes included pain scores and quality of recovery. Data from 86 women were analysed. Median (IQR [range]) 24‐h morphine consumption was similar in patients receiving quadratus lumborum block and sham block (12 (8–29 [0–68]) mg vs. 14 (5–25 [0–90]) mg, respectively; p = 0.986). There was a reduction in median (IQR [range]) visual analogue scale pain scores at 6 h with quadratus lumborum block compared with sham block both at rest (6 (0–14 [0–98]) mm vs. 14 (3–23 [0–64]) mm (p = 0.019); and on movement: 23 (10–51 [0–99]) mm vs. 44 (27–61 [2–94]) mm; (p = 0.014)). There was no difference in pain scores at any other time‐point up to 48 h. When used in conjunction with intrathecal morphine and spinal anaesthesia, bilateral quadratus lumborum block does not reduce 24‐h morphine consumption after caesarean section.